Sentiment Analysis on Gold Currency - Anisa Mujahidah; Lina Marlina (SMART Insight, 2020)
This research was conducted to examine the Gold Currency in the scope of the economy in terms of scientific research in published journals and indexed by Scopus. The method used is sentiment analysis from secondary data in the form of 100 journals published in the last three years and then processed using Ms. software. Excel 2016 and SentiStrength. The results show that research on Gold Currency in the scientific literature has increased. The sentiment analysis results show a tendency for negative perceptions in the scientific literature towards Gold Currency, with negative high sentiment of 1% and negative sentiment of 36%. The neutral sentiment at 43%, then positive sentiment at 20%. The benefit of this research is for literature material and considerations related to Gold Currency. As well as efforts to find out the threats, negative perceptions, and shortcomings of Gold Currency. In addition, to find out positive perceptions, advantages and benefits of Gold Currency.